Distributed systems architecture a middleware approach - Puder, Arno; Römer, Kay; Pilhofer, Frank (Morgan Kaufmann/Elsevier, 2006)
This guide to building robust distributed software includes a complete open source CORBA system.
Title from title screen. - Includes bibliographical references and index
Keywords: Electronic data processing -- Distributed processing; Computer architecture; CORBA (Computer architecture); Traitement réparti; Ordinateurs; Architecture; CORBA (Architecture d'ordinateurs); Electronic data processing; Distributed processing